Beyond imagery: new approaches to the analysis of literary antisemitism and a casestudy of Thomas Mann's Buddenbrooks - Marquardt, Franka (Nordisk judaistik/Scandinavian Jewish Studies, 2000)
The most common approach when analyzing literary antisemitism is to explore the “image of the Jew” in literary texts. At a closer look, this focus entails several problems, ranging from a neglect of other anti-Semitic elements in the text, to the risk that this method results in reproducing these anti-Semitic patterns of thought. By questioning this method, the focus shifts to other levels in the literary texts, which may reveal an anti-Semitic “sub-text” although the imagery seems harmless. What these literary levels are and how they interact is exemplified by two examples from Thomas Mann’s Buddenbrocks. The results shed new light on his Nobel prize-winning first novel.